Improving English Reading Skills through Task-Based Learning in ecuadorian High Schools - Cabrera Salavarría, Kerly María; Recalde García, Frans Andrés (Arandu UTIC, 2025)
Reading skills enhance the comprehension of paragraph structures, communication, and decision-making. Developing strong English skills in reading is significant for teaching in high school students. Task-Based Learning (TBL) bestows an innovative approach by involving students in practical, meaningful tasks that promote active learning and cognitive development. This study delves into the effects of TBL on high school students' English reading skills, in other words the purpose of this study is to analyze the impact of TBL focusing on reading skills such as improvements in comprehension, engagement, motivation, and higher-order thinking abilities. The study uses pre- and post-tests in a sample of 22 eighth-grade students of Emilio Isaías Abihanna´s High School to demonstrate that integrating TBL into reading skills enhances students’ proficiency. Also, it includes Lewin´s (1946) and Elliot´s (2014) teaching model to follow up four stages in which students can have the opportunity to improve their knowledge.